A review of CONCEPTT study findings including subanalyses in pregnant women using continuous glucose monitoring with type 1 diabetes and their offspring - David Q Pham; Ashley Thorsell; Kristin Castorino; Brandon Cobb (Endocrine Connections, 2024)
The main objective of this article is to provide a comprehensive review of continuous glucose monitor (CGM) use in pregnant women with type 1 diabetes (T1D) from the CONCEPTT study including subanalyses. Literature search was accessed through MEDLINE (1966–September 2023) using the key terms: CONCEPTT, pregnancy, women, T1D, and CGM with limitations set to distinguish human subjects written in English. A total of 17 publications including one main clinical trial and 15 subanalyses have been published to date regarding the use of CGM in pregnant women with T1D which were conducted by a research group identified as the CONCEPTT Collaborative Group. While advances in maternal care have resulted in safer pregnancy for both the mother and child, women with preexisting T1D and pregnancy still experience higher rates of complications both in the short and long term. The use of CGM in pregnancy has not been studied extensively until more recently. The CONCEPTT clinical trial was a landmark study that involved several subanalyses. The main trial proved that CGM use in T1D pregnancy resulted in less hyperglycemia in the third trimester, reduced large for gestational age (LGA, >90th percentile), reduced neonatal intensive care unit admissions lasting longer than 24 h, and reduced neonatal hypoglycemia. Although subanalyses showed a variety of results including ‘inconclusive’ due to lack of prespecification, it is believed that CGM in T1D during pregnancy is to be recommended and used for overall improved outcomes.